Effect of Fresh Frozen Plasma Transfusion on Electrochemical Parameters of Blood Plasma in Patients with Severe Combined Trauma - I. V. Goroncharovskaya; A. K. Evseev; A. K. Shabanov; V. V. Kulabukhov; A. N. Kuzovlev; K. A. Popugaev; S. S. Petrikov (Общая реаниматология)
Purpose: to study the dynamics of blood plasma electrochemical parameters in patients with severe combined trauma before and after fresh frozen plasma (FFP) transfusions.Materials and methods. The open circuit potential (OCP) of platinum electrode and antioxidant activity of blood plasma were studied in 35 patients with severe combined trauma and 35 post-FFP samples with at least 6-month shelf life. The electrochemical parameters of patients’ blood plasma were analyzed before transfusion, and 1 hr. and 24 hrs. after transfusion.Results. OCP measured in FFP was found to be more positive vs. OCP measured in recipients' blood plasma in 34 out of 35 cases (97%). It has been shown that in patients with severe combined trauma, OCP increased from 5.047 [-7.553; 12.976] mV to 12.827 [-1.372; 24.764] mV and antioxidant activity decreased 24 hours after FFP transfusion from 16.979 [11.302; 20.946] µC to 13.551 [9.288; 18.405] µC. After FFP transfusion, there were no signiﬁcant changes in clinical blood parameters.Conclusion. By measuring electrochemical parameters of blood plasma in patients with severe combined trauma before and after FFP transfusions, it was discovered that in spite of absence of changes in blood parameters by routine methods, there are changes in the condition of the antioxidant system of the body, which manifest in the bias of patients’ blood plasma OCP towards higher positive values and decreased antioxidant activity. Redox imbalance in the body might cause the oxidative stress development.